Table-top, full-field, actinic microscope for extreme ultraviolet lithography mask characterization - Brizuela, Fernando, author; Rocca, Jorge J., advisor; Marconi, Mario C., committee member; Lundeen, Stephen, committee member; Attwood, David T., committee member (Colorado State University. Libraries, 2010)
The development of increasingly smaller, faster, and more complex electronic devices that significantly impact everyday life is driven by the ability of printing smaller and smaller components onto semiconductor chips. The number of transistors printed onto an integrated circuit has increased from about one thousand in the 1970 to over a billon in recent years. This exponential growth has been possible thanks to great advances in microlithography processing, and is expected to continue with the implementation of Extreme Ultraviolet Lithography (EUVL) for the printing of the next generation of semiconductor chips. Although EUVL is conceptually similar to conventional lithography in that a mask is projected onto the wafer with a set demagnification, the unique characteristics of extreme ultraviolet light have generated a myriad of technological challenges in the development of this new lithographic technique, including the availability of bright sources, photoresists, reflective optics, and metrology tools at these wavelengths. Of these challenges, the need for microscopes capable of characterizing the printability of absorber patterns on the reflective Mo/Si coated lithographic masks, has risen be to one of the highest priorities for chip manufacturers as they prepare to implement EUVL at high-volume manufacturing. Currently, only a very limited number of EUV microscopes for mask characterization are available. And although these few synchrotron-based microscopes have significantly contributed to the development of EUVL masks, their building-size illumination source make them unsuited for mask characterization in an industrial setting. This dissertation describes the development of the first compact, full-field microscope for at-wavelength characterization of EUVL masks. This microscope combines the output of a table-top 13.2 nm wavelength laser with state-of-the-art diffractive optics to render high quality images of the patterns on EUVL masks with 55 nm spatial resolution and acquisition times of less than 90 seconds. From these images we have demonstrated for the first time measurements of line-edge roughness and normalized intensity line slope of an EUVL mask using a compact microscope. This is significant because with this microscope that emulates the imaging conditions of a 4xdemagnification stepper it is possible to evaluate the mask quality and printability independently of photoresist response. It is foreseeable that these microscopes will not only contribute to the development of EUVL mask technology, but will also play a significant role in the path for the realization of convenient stand-alone metrology systems for on-site evaluation of EUVL masks.
Covers not scanned.
Keywords: Extreme ultraviolet lithography; Ultraviolet microscopy; Lasers in engineering